2013
DOI: 10.1002/jpln.201300154
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochar amendment promotes microbial immobilization of mineral nitrogen

Abstract: Hydrochars and biochars are products of the carbonization of biomass in different conversion processes. Both are considered suitable soil amendments, though they differ greatly in chemical and physical composition (e.g., aromaticity, inner surface area) due to the different production processes (pyrolysis, hydrothermal carbonization), thus affecting their degradability in soil. Depending on the type, char application may provide soil microorganisms with more (hydrochars) or less (biochars) accessible C sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 26 publications
8
54
0
Order By: Relevance
“…In both cultivation periods, the N content depended on the hydrochar concentration in the soil. Incubation experiments with hydrochar addition to sandy soil confirmed the high N-immobilization potential of hydrochars and showed a promotion of soil microbial biomass after hydrochar addition (Bargmann et al, 2014a). Nitrogen immobilized during the first 8 weeks of cultivation was not released during the second cultivation period, and an additional fertilizer application was insufficient to cover the crop's N demand.…”
Section: Nitrogen Availabilitysupporting
confidence: 51%
See 1 more Smart Citation
“…In both cultivation periods, the N content depended on the hydrochar concentration in the soil. Incubation experiments with hydrochar addition to sandy soil confirmed the high N-immobilization potential of hydrochars and showed a promotion of soil microbial biomass after hydrochar addition (Bargmann et al, 2014a). Nitrogen immobilized during the first 8 weeks of cultivation was not released during the second cultivation period, and an additional fertilizer application was insufficient to cover the crop's N demand.…”
Section: Nitrogen Availabilitysupporting
confidence: 51%
“…As demonstrated in earlier studies with hydrochars, soil amendment with hydrochars can negatively affect the germination of various plants (Bargmann et al, 2013) and decrease the mineral-N concentration in soil (Bargmann et al, 2014a), thus limiting the plant's N uptake (Bargmann et al, 2014b). Although these results are supported by the studies of , Busch et al (2012), and Nelson et al (2011), and have also been reported for biochars (Clough and Condron, 2010), there is currently no information available regarding the persistence of these effects.…”
Section: Introductionmentioning
confidence: 57%
“…Compared to control soils increasing amounts of fermented HTC lead to a higher shoot biomass and shoot: root ratio, likely due to its low C:N ratio that fostered microorganisms and in turn wheat growth (Bargmann et al, 2014). Moreover, P. fimata abundance declined by about half, and, as roots can serve as diet (Endlweber and Scheu, 2006;Ngosong et al, 2014), reduced grazing pressure may have additionally enhanced wheat growth.…”
mentioning
confidence: 98%
“…Compared to biochar, hydrochar decomposition in soil is generally faster due to the less aromatic structure and higher content of labile C fractions (Steinbeiss et al, 2009;Cao et al, 2010;Libra et al, 2011). Thereby hydrochar provides often more accessible C and N resources to microorganisms (Bargmann et al, 2014), which also may affect their animal grazers.…”
mentioning
confidence: 99%
“…HTC was found to have positive effects on growth, root colonization and spore germination of mycorrhizal fungi (Rillig et al 2010;Salem et al 2013b) as well as on the activity and abundance of SMB (Bargmann et al 2014). Negative effects of HTC on mycorrhiza have also been reported, pointing to the occurrence of toxic compounds, mostly present in the water soluble carbon fraction (George et al 2012), whereas collembola ingested and digested unwashed HTC without being negatively affected and may even derive nutritional benefits from it (Salem et al 2013a).…”
Section: Introductionmentioning
confidence: 94%